2019
DOI: 10.1111/eve.13176
|View full text |Cite
|
Sign up to set email alerts
|

Recumbency following diagnostic analgesia of the sacroiliac joint regions: 15 horses

Abstract: Sacroiliac (SI) joint region pain is relatively common in sports horses and diagnosis is ideally confirmed by diagnostic analgesia (SI joint region blocks). Anecdotal reports describe complications following SI joint region blocks, but there is no detailed published information. Our aim was to document a series of horses that became recumbent following SI joint region blocks. Clinicians were asked to participate via the email list of the American College of Veterinary Sports Medicine and Rehabilitation and by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Only horses in Group 1 underwent diagnostic anaesthesia of the sacroiliac joint regions, a technique which is not specific for either the sacroiliac joint or the caudal lumbar symphyses. However, we do advocate performing periarticular anaesthesia of the sacroiliac joints as a method of confirming the general region of pain and have demonstrated that it is relatively safe (Nagy and Dyson ). It is not possible to determine definitively the contribution to pain of the lesions identified, and this may have differed between Groups 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Only horses in Group 1 underwent diagnostic anaesthesia of the sacroiliac joint regions, a technique which is not specific for either the sacroiliac joint or the caudal lumbar symphyses. However, we do advocate performing periarticular anaesthesia of the sacroiliac joints as a method of confirming the general region of pain and have demonstrated that it is relatively safe (Nagy and Dyson ). It is not possible to determine definitively the contribution to pain of the lesions identified, and this may have differed between Groups 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rate of 0.70% per horse (2/284) correlates well with the prevalence identified in this study; however, the main difference between this study and the current data is that a different SIRA technique was used [ 1 ]. A recent study [ 10 ] reported a within-clinic recumbency rate of approximately 0.3% (3 out of approximately 1180) following SIRA, with the authors estimating 1–2% of horses showed mild ataxia that precluded ridden re-evaluation [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ataxia and recumbency are the most frequently reported complications and are reported to be quick in onset following SIRA, with the majority of horses noted to be ataxic or become recumbent within 20 minutes [ 1 , 10 ]. The one horse that displayed a mild gait abnormality in this study was identified when re-evaluated ten minutes following the block, which correlates with the previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations